'Border' matters in discussions of cross-border students. Issue 1 (2nd May 2017) - Chan, Anita Kit-Wa; Ngan, Lucille Lok-Sun; Wong, Anthony K.W.; Chan, W.S.
Abstract : Purpose: Cross-border students – children who are permanent residents of Hong Kong but live on the mainland and travel across the border to school every day – have been an important social, educational and political issue in Hong Kong. Nevertheless, current discussions regarding this issue focus mainly on the group of students whose parents are Chinese residents and seldom examine the wider contribution of social, geo-political, global-economic and policy changes to the phenomenon. These shortcomings have limited the understanding of the role of the state and the varied needs of these child migrants from diverse family backgrounds. This paper aims to address these gaps. Design/methodology/approach: It proposes to bring changing border and immigration policies in Hong Kong back into the current analysis and offers a case study of border history. It revisits publications on Hong Kong's immigration and migration policies, official statistics and government policy papers and (re)constructs the border changes that took place during the period from 1950 to 2013, which led to the rise and complexity of cross-border students. Findings: This critical historical review offers two important findings: First, it reveals how the government, through its restrictive and liberalized border regulations, has constrained and produced different types of cross-border families. Second, it shows that cross-border students come from diverse family configurations, which have adopted cross-border schooling as a family strategy. Originality/value: These findings underscore the importance of historical perspective, the wider context in migration studies, the centrality of the state in migrant families and a differentiated understanding of child migrants.